A summary of the research on the foundation and application of blockchain technology. (December 2020) - Gai, Rongli; Du, Xiaoyan; Ma, Shuya; Chen, Na; Gao, Shouchuan
Abstract: Blockchain is an emerging distributed database technology. It has the characteristics of decentralization, non-tampering, traceability and final consistency. Blockchain can solve data management problems in untrusted environments. Based on the research and analysis of the blockchain system, this article expounds the application of the blockchain system in the distributed database environment. First, this article introduces the concept of the blockchain system and the classification of the blockchain system from multiple aspects. Then it introduces the data storage technology and data encryption technology adopted by the blockchain system in detail. Finally, the application prospects of the blockchain system in today's society are introduced.